CT Scan importance in the first eight hours of head injury - Alfageeh, Mohammed; Bahran, Moneerah; Albargi, Sultan; Althomali, Ibrahim; Alzahrani, Adnan; Al-Buqaisi, Amal; Al-Ramadhan, Mahdi; Hussain, Abdullah; Alghamdi, Abdullah; Alsuhaibani, Khalid (International Journal of Advances in Medicine, 2018)
Traumatic brain injury following head injury is a major public health problem that can result in significant long-term morbidity and mortality among adults and children worldwide. Emergency brain imaging is necessary for individuals subjected to traumatic brain injury to early detect treatable conditions. Prompt neurosurgical management of treatable conditions can prevent further damage and secondary neurological deficits. This will subsequently improve the outcome and reduce long-term disability. Computed Tomography (CT) of the brain is the investigation of choice for assessment of patients with head injury due to its availability, advantages, and sensitivity for multiple lesions following head trauma. This article will review and discuss the importance of CT imaging in evaluating patients with traumatic brain injury, its advantages, limitations, and prognostic values.